Clinico-hemato-biochemical profile of dogs with liver cirrhosis - Elhiblu, M. A. (Vet World, 2015)
AIM: The aim of this study was to determine the relevant tools in the diagnosis of liver cirrhosis in dogs. MATERIAL AND METHODS: A total of 140 dogs presented at Veterinary Teaching Hospital, Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana, showing clinical signs of hepatic insufficiency were subjected to clinico-hemato biochemical, urological, ultrasonographic (USG), and USG guided fine-needle biopsy examinations by standard methods. On the basis of these results, 6 dogs out of 140 dogs were found to be suffering from liver cirrhosis. Six clinically healthy dogs constituted the control group. RESULTS: The dogs suffering from liver cirrhosis manifested inappetence, halitosis, abdominal distension, weight loss, melena, icterus, anemia, and neutrophilic leukocytosis with the left shift. Levels of hemoglobin, lymphocytes, packed cell volume, mean corpuscular volume, mean corpuscular Hb (MCH), and platelet count were significantly lower in liver cirrhosis group than control group while total leukocyte count, neutrophils, and MCH concentration were significantly higher. Glucose, total protein, albumin, A/G ratio, and fibrinogen were significantly lower, and creatinine, alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, prothrombin time, and APTT were significantly higher than the control values. Ultrasound revealed diffuse increase in echogenicity with rounded and irregular liver margins. Cytological examination of the ascitic fluid and fine-needle aspiration biopsy of liver was not fruitful in the diagnosis of liver cirrhosis. CONCLUSIONS: Liver cirrhosis causes clinical and hemo-biochemical alterations, which require special consideration when treating diseased animals. USG, diffuse increase in echogenicity of liver, rounding and irregularity of liver margins and microhepatica were the consistent findings. It is suggested that USG along with hemo-biochemical alterations may be used as a diagnostic tool for liver cirrhosis in dogs.